Fast electrothermally activated micro-positioner using a high-aspect-ratio micro-machined polymeric composite - Lau, Gih Keong (2013)
Recently, silicon electrothermal micro-actuators have been developed for dual-stage micropositioning in hard disk drive. But, silicon with a low coefficient of thermal expansion (CTE) has a shortcoming of requiring a large temperature change (>300 °C) to expand adequately. This letter presented a high-CTE polymer composite to solve the shortcoming of silicon. The polymer composite consists of high-aspect-ratio micro-machined SU-8 thermal expander and silicon thermal conductor. A micro-positioner which embodies the proposed polymer composite can drive a slider to travel fast (>1 kHz) more than a 17 nm-pitch data track under a moderate temperature rise (<100 °C).